Design Processes For Web-Based Hypermedia Engineering. - Jantan, Azrul Hazri; Sumari, Putra; Sulaiman, Shahida (2007)
The process of designing and developing hypermedia applications is one of the big challenges for today’s hypermedia engineering industry.